Geochemical comparison of eastern and western meta-igneous rocks from Lützow-Holm Complex, East Antarctica - Awata, Hikari; Kamei, Atsushi; Hokada, Tomokazu; Baba, Sotaro; Kitano, Ippei; Dashbaatar, Davaa-ochir; Setiawan, Nugroho; Nantasin, Prayath; Motoyoshi, Yoichi (2018)
The Ninth Symposium on Polar Science/Ordinary sessions: [OG] Polar Geosciences, Wed. 5 Dec. / Entrance Hall (1st floor), National Institute of Polar Research conference object